Yeast ASF1 protein is required for cell cycle regulation of histone gene transcription. - Sutton, A (2001)
Transcription of the four yeast histone gene pairs (HTA1-HTB1, HTA2-HTB2, HHT1-HHF1, and HHT2-HHF2) is repressed during G1, G2, and M. For all except HTA2-HTB2, this repression requires several trans-acting factors, including the products of the HIR genes, HIR1, HIR2, and HIR3. ASF1 is a highly conserved protein that has been implicated in transcriptional silencing and chromatin assembly. In this analysis, we show that HIR1 interacts with ASF1 in a two-hybrid analysis. Further, asf1 mutants, like hir mutants, are defective in repression of histone gene transcription during the cell cycle and in cells arrested in early S phase in response to hydroxyurea. asf1 and hir1 mutations also show very similar synergistic interactions with mutations in cac2, a subunit of the yeast chromatin assembly factor CAF-I. The results suggest that ASF1 and HIR1 function in the same pathway to create a repressive chromatin structure in the histone genes during the cell cycle.